2018
DOI: 10.17507/tpls.0808.05
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of the Relationship among EFL Learners’ Autonomy, Self-esteem, and Choice of Vocabulary Learning Strategies

Abstract: This study seeks to determine whether any significant relationship exists among EFL learners’ autonomy (LA), self-esteem (SE), and choice of vocabulary learning strategies (VLS) as well as whether LA and SE are predictors of these strategies. To achieve these aims, this study employed a descriptive research design. Participants included 157 male and female undergraduate EFL learners, all within the age range of 17 to 25 years. They were studying English within the sub-disciplines of English Literature, Linguis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…This finding aligns with some research saying that this strategy is favored to be implemented by freshmen students (Alqarni, 2018). Other studies also show that this strategy is preferable to use, although it is not the most frequently implemented (Bytheway, 2015;Ghalebi et al, 2020;Tilfarlioglu & Sherwani, 2018). This strategy builds more robust engagement among learners and teachers through interaction.…”
Section: Social Strategysupporting
confidence: 87%
See 1 more Smart Citation
“…This finding aligns with some research saying that this strategy is favored to be implemented by freshmen students (Alqarni, 2018). Other studies also show that this strategy is preferable to use, although it is not the most frequently implemented (Bytheway, 2015;Ghalebi et al, 2020;Tilfarlioglu & Sherwani, 2018). This strategy builds more robust engagement among learners and teachers through interaction.…”
Section: Social Strategysupporting
confidence: 87%
“…Therefore, the learners tried to find the meaning from other sources and then conclude based on their reading. This strategy is also widely used, especially for university students who encounter this situation (Ghalebi et al, 2020;Tilfarlioglu & Sherwani, 2018). A study conducted by Yaacob et al (2019) showed that the guessing strategy was mainly used before the dictionary strategy (Ghalebi et al, 2020;Tilfarlioglu & Sherwani, 2018).…”
Section: Guessing Strategymentioning
confidence: 99%
“…In the literature there are numerous studies on learner autonomy in foreign or second language context (Abadi & Baradaran, 2013;Almusharraf, 2018;Balçıkanlı, 2008b;Dişlen-Dağgöl, 2022;Elizondo & Garita, 2013;Kartal & Balci, 2021;Korlu & Mede, 2018;Sedighi & Tamjid, 2016;Shams, 2013;Tilfarlioglu & Sherwani, 2018;Tseng, Liou &Chu, 2020;Vela & Rushidi, 2016;Tran, 2020;Yıldırım, 2008).…”
Section: Previous Studies On Learner Autonomymentioning
confidence: 99%
“…They also noted that for EFL learners to improve their pronunciation, self-governing and self-confidence tactics were necessary. According to Tilfarlioglu and Sherwani (2018), there is a relation between learner autonomy, confidence, and vocabulary learning strategies.…”
Section: Introductionmentioning
confidence: 99%